Características do trabalho docente e gênero: um estudo sobre os professores da Educação Básica do Brasil (2007-2014) - Juliana de Jesus Silva (2017)
The teachers of Basic Education have experienced in recent decades the transformations that have occurred in the Brazilian educational sector. Such changes have brought consequences to the work process, as well as reflections on the health of these workers. Historically, women work in more precarious conditions and experience worse conditions of insertion in the labor market in relation to men, including in the teaching career. Studies analyze in a limited way the characteristics of the teachers of Basic Education, especially with regard to the conceptions of gender. The objectives of this study were: 1) To study the demographic and occupational characteristics of the Basic Education teachers in Brazil; 2) Analyze possible gender cuts in the conformation of the category. This was a quantitative study of the characteristics of Basic Education teachers conducted between 2007 and 2014. Data on demographic and occupational characteristics were collected through the microdata of the School Census of Basic Attention, carried out by the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP). It was verified the predominance of teachers working in Basic Education, as already evidenced in other studies, which reinforces the feminization of teaching work. During the period under study, there was an increase in the number of teachers of higher ages for both sexes. Male teachers focused on the more advanced stages of education and women in the early stages. Men taught in more schools and classes. The women concentrated on teaching in smaller classes and men in larger classes. Regarding the employment relationships, there was a tendency for both sexes to increase in those working in the private network and decrease in those linked to the public network. The stable bond was the most frequent, however, there was an increase of teachers, of both sexes, with temporary contract. Finally, there was an increase in the number of outsourced teachers and teachers. Although the literature shows that women experience worse working conditions, in the present study it was possible to verify the great performance of men in more than one school, in a larger number of classes and with multiple job links. It is important to better explore the subject to deepen the knowledge regarding the trends verified. The information produced from the present study can base the planning of public policies focused on the working conditions and satisfaction of the studied population